Pelatihan Penulisan Judul Dan Introduction Dalam Karya Ilmiah Bagi Mahasiswa - Sitti Pratiwi Husain; Sri Desiyani Permata Gani; Dhea Safitri Kurniawati Mohama (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2021)
Scientific work is the result of writing that presents opinions, observations, reviews and research in a particular field by paying attention to norms and ethics for writers. participants in determining the title and making the introduction properly and correctly according to the guidelines for writing scientific papers. The target audience in the service activities are students in the Faculty of Economics, especially the Accounting Study Program who will be in charge of the proposal proposal seminar. The methods used in this training activity are as follows: Lecture method, discussion method, and exercises. Evaluation in this activity is carried out in three stages, namely the activity planning stage, the stage during the activity process, and the final stage of the activity. The results of this activity provide great benefits for the training participants who in this case are students in the process of making scientific papers starting from determining the problem, formulating titles, writing introductions as well as references and research data, so that scientific works produced by students become quality scientific work.